Liposarcoma of the small bowel. Intestinal intussusception in the adult. - Rodríguez, José L; Piñeyro, Alberto; Tarocco, Luis A; Fein, Celia; Navarrete, Héctor (Cirugía del Uruguay, 1987)
A case of jejunal intussusception due to a primitive liposarcoma of the small bowel is presented. A extense review of local and foreign bibliography is done. The